A pilot randomized study comparing two methods of non‐invasive ventilation withdrawal after acute respiratory failure in chronic obstructive pulmonary disease. Issue 5 (21st June 2013) - Lun, Chung‐Tat; Chan, Veronica L.; Leung, Wah‐Shing; Cheung, Alice P.S.; Cheng, Suet‐Lai; Tsui, Miranda S.N.; Chu, Chung‐Ming
Abstract Background and objective Patients with chronic obstructive pulmonary disease (COPD) presenting with acute hypercapnic respiratory failure (AHcRF) benefit from non‐invasive ventilation (NIV). The best way to withdraw NIV is not known, and we conducted a pilot study comparing stepwise versus immediate withdrawal of NIV in these patients. Methods This was a prospective, single‐centre, open‐labelled randomized study comparing stepwise versus immediate withdrawal of NIV in patients with COPD exacerbation recovering from AHcRF. The primary end‐point was the success rate of NIV withdrawal, defined as no restarting of NIV from randomization to 48 h after complete withdrawal of NIV. Results Sixty patients were randomized, 35 patients to stepwise withdrawal and 25 patients to immediate withdrawal. The two study arms were clinically comparable. There was no statistically significant difference in the success rate, with NIV successfully stopped in 74.3% and 56% in the stepwise and immediate withdrawal groups, respectively (P = 0.139). Conclusions We could not show any benefits for either strategy to withdraw NIV. The study may have been underpowered to detect differences, and larger prospective studies are required.